Actas del Primer Encuentro Cuerpo, educación y sociedad: Debates en torno al cuerpo (2016 : Ensenada) - Escudero, Carolina (Coord.) (Trabajos, comunicaciones y conferencias, 2018)
This book contains the papers presented at the 1st Encuentro Cuerpo, educación y sociedad (Ensenada, November 7-9, 2016). The themes addressed in them are more or less directly linked to the research topics that are developed in the Interdisciplinary Center for Body, Education and Society.